Preparation And Evaluation Of Polyherbal Scented Candle Using Volatile Oils Extracted By Enfleurage Method: Evaluation Of Polyherbal Scented Candle - Thimmapuram, Usha Kiran Reddy (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2024)
Background: Medicinal plants serve dual roles, offering remedies for various diseases and income-generation opportunities. Ancient Indian texts, including Ayurveda, extensively document plant use in healthcare. Globally, medicinal plants are vital resources in the fight against severe diseases. Essential oils in plants provide distinct aromas, flavors, and pathogen protection. Tithonia erecta flower oil boasts a complex composition with diverse beneficial properties. Exocarp extract from Citrus sinensis differs from juice or leaf extracts, containing more lipophilic compounds but fewer glycosylated compounds and lacking cyanidins and sterols. Eucalyptus globulus oil acts as an antiseptic and anti-spasmodic stimulant for respiratory issues. Scented candles are a popular relaxation method, promoting well-being through ambient lighting. This study aims to create practical scented candles using natural materials like soy wax, beeswax, and essential oils. Methods: The desired candle should offer a long burn time, be cost-effective, and pose no health risks to users. The candle composition includes gel wax, vegetable or animal fat, eucalyptus leaves, marigold petals, and orange peels. This study involves preparing and evaluating polyherbal scented candles using volatile oils extracted through the enfleurage method. Results: The phytochemical analysis of these extracts revealed the presence of volatile oils, alkaloids and proteins. The FTIR analysis reveals the presence of OH group in these extracts. Conclusion: This research successfully developed a natural polyherbal scented candle with extended burn time, cost-effectiveness, and user safety. Antioxidants prevent undesired changes during production and use. The candle contains gel wax, vegetable or animal fat, eucalyptus leaves, marigold petals, and orange peels. Evaluation tests confirmed safety and effectiveness. Among formulations, F1 is fragrance-minimal and allergy-free, while others may cause counter-irritation. This eco-friendly product provides a fresh herbal fragrance for stress relief and is competitively priced.